Letramentos digitais em narrativas de estudantes de licenciatura em pedagogia EaD - Silva, Iracema Cristina Fernandes da (2020)
This Master’s thesis presents the results of research carried out in the graduate program about education (PPGE), from federal university of Mato Grosso (UFMT), in the school organization research line, training and pedagogical practices, within the research group Information Laboratory of Studies on Information and Communication Technology in Education (LêTece). The communication process with the use of digital Technologies on education has been going through significant changes, mainly in distance education (EaD) wo seeks support for digital cultural artifacts to break with logic of time and space historically built. The hibridization of digital Technologies has provided a great mobility in everyday communication practices and has allowed to enlarge the discussion about such concepts and their relationships with education. In this direction the study had as a problem: digital literacies (LD) are required for undergraduate students, distance mode, can act competently in the course mediated by learning environment (AVA)? Looking for answers to such a question the purpose of the research is to understand about uses and appropriations of tecnologies in digital narratives of the students in the class 1/2017, in the pedagogy course, distance modality NEAD-UFMT, Pole of Juara, relating to digital literacies (LD), in a social perspective and critical approach through the ideological model. The investigation is based on the qualitative research approach (DENZIN E LINCOLN, 2006), and inspiration the research methodology of search-formation in cyberculture (SANTOS, 2014). The option for this kind of metodology was to provide a dialogical movement to research and graduate and research, graduate and graduate the others at the same time, imbricate in the social relation and pedagogical- didactics with the search object. The theoretical framework to discuss cyberculture, digital tecnologies, online education, digital literacies was based on authors like Street (2014), Buzato (2009), Santos (2012), Souza (2016) and others. Beyond the bibliographic study, two systematic literature reviews were performed, to broaden the look on the brazilian searches in education, cyberculture, teacher training and digital literacies (LD). The document analysis was based on the pedagogical course Project quoted, and student memories and student-produced blog narratives on two AVA interfaces, composing the “corpus” of study analysis in this study. The results show that the materialized curriculum in the PPC of the course don’t include a Specific module or discipline to work using digital technologies in AVA. But there is however, the formation, “Introduction to the virtual learning environment Moodle”, that precedes curriculum subjects with potencial to mobilize, at least, two dimensions from the digital literacies, the functional and communicational. The student’s memories – written narratives – made by students in the beginning of the course, mention the use of technologies such as the mimeograph, use of lan house, cell phones, notebooks, and social networks like facebook and WhatsApp, as well as unfamiliarity and difficulties in the use of digital technologies and virtual platforms during the school formation that preceded the course.In blog narratives, the students raised questions about computer access, cell phone and internet and the gradual acquisition of new technological artifacts for more intense use in the course and in your daily social practices. The WhatsApp, the telegram and the e-mail were the mediating devices in the teaching-learning process in addition to AVA during the course. The research demonstrated that the practices of using digital technologies throughout the course has been mobilizing knowlodge that has gone beyond the functional communicational dimensions, reaching other dimensions such as informational, social, self-management, self-direction, cognitive, online communication, as well as other languages, modes of expression and interaction that emerged like ubiquitous communication, the multimodality, the fake news, the games and the avatars, being possible to understand that the daily appropriations with the use of TD potentialize and expand the LD in the social and educative practices.